Family Arena as a Habituation of Pluralism Values in Social Behavior of Pantura Youth, Banyutowo Village, Dukuhseti District, Pati Regency - Lutfiana, Hilma; Atmaja, Hamdan Tri; Sanjoto, Tjaturrahono Budi (Universitas Negeri Semarang, 2021)
Starting from the concern of rampant conflict of identity differences today. The character of the coastal community who is firm, tough and open to access will easily accept the development of knowledge, technology and differences. The diverse ideologies of the Banyutowo people does not rule out the effect on the split. The cultivation of values ​​and norms are the role of the family arena, considering that the family is the first and foremost agent of socialization for children. The role of the family arena in the habituation of pluralism is an urgent matter that can be inherited to Banyutowo youth as the nation's successor. The purpose of this research were to analyze the role of the family arena in the habituation of pluralism values ​​in adolescents and to identify the implementation of adolescent social behavior. Data were collected by interview, observation and documentation study. Then followed by a qualitative descriptive data analysis following the concept of Miles and Huberman. The results showed that Muslim families, GITJ Christians and Bethany Christians played two roles, that are providing knowledge and evaluation, but those roles were not maximal for adolescents whose parents worked as fishermen, due to the intensity meeting that rarely. Meanwhile, the habituation of family pluralism values ​​in the social behavior of Muslim adolescents, GITJ Christians and Bethany Christians includes: prioritizing the tolerance value, prioritizing the mutual respect value, prioritizing the life pride value in plurality, prioritizing the high social value ​​and promoting the togetherness value in social relationships. With the habituation process, the value of pluralism in the family is expected that Banyutowo adolescents have positive social behavior as a provision in understanding plurality.